2005
DOI: 10.1200/jco.2005.04.358
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bcl-2 in Classical Hodgkin's Lymphoma: An Independent Predictor of Poor Outcome

Abstract: Expression of bcl-2 in CHL is a useful, independent prognostic marker and can be used in association with clinical parameters to identify newly diagnosed patients with a good, intermediate, or poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 18 publications
3
42
1
Order By: Relevance
“…1,2 György et al recently reported in Blood that measuring MP by flow cytometry was flawed because of the overlapping biophysical properties of immune complexes, causing false-positive signals during analysis of synovial fluid from patients with rheumatoid arthritis. 3 They suggested that similar problems might occur during analysis of circulating MP from patients with acute coronary syndrome, where the presence of circulating immune complexes has been reported, 4 therefore raising a question on the validity of previous reports. 3 In view of György et al's findings, we investigated the potential interaction of immune complexes with flow cytometry analysis of circulating MPs in patients with coronary artery diseases, using MP sensitivity to a brief exposure to Triton detergent.…”
Section: To the Editormentioning
confidence: 97%
See 2 more Smart Citations
“…1,2 György et al recently reported in Blood that measuring MP by flow cytometry was flawed because of the overlapping biophysical properties of immune complexes, causing false-positive signals during analysis of synovial fluid from patients with rheumatoid arthritis. 3 They suggested that similar problems might occur during analysis of circulating MP from patients with acute coronary syndrome, where the presence of circulating immune complexes has been reported, 4 therefore raising a question on the validity of previous reports. 3 In view of György et al's findings, we investigated the potential interaction of immune complexes with flow cytometry analysis of circulating MPs in patients with coronary artery diseases, using MP sensitivity to a brief exposure to Triton detergent.…”
Section: To the Editormentioning
confidence: 97%
“…3 They suggested that similar problems might occur during analysis of circulating MP from patients with acute coronary syndrome, where the presence of circulating immune complexes has been reported, 4 therefore raising a question on the validity of previous reports. 3 In view of György et al's findings, we investigated the potential interaction of immune complexes with flow cytometry analysis of circulating MPs in patients with coronary artery diseases, using MP sensitivity to a brief exposure to Triton detergent. 3 Ten patients with acute coronary syndromes (ACS) were included according to their clinical characteristics.…”
Section: To the Editormentioning
confidence: 97%
See 1 more Smart Citation
“…Although several reports found a significantly negative prognostic effect of its over-expression in Hodgkin/Reed-Sternberg cells, [28][29][30][31][32][33] other studies found no impact. [34][35][36] Possible reasons for the inter-study discrepancy include disparate study populations, technical differences, for example, different antibody clones, use of tissue microarray vs whole sections, inter-observer variability, different criteria of BCL2 positivity, and disparate use of the index of outcome.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have analyzed the clinical relevance of the expression of cell cycle and apoptosis regulators in cHL using IHC or gene expression profiling (Brink et al, 1998;Devilard et al, 2002;Garcia et al, 2003;Montalban et al, 2000;Morente et al, 1997;Smolewski et al, 2000). Shorter survival was significantly associated with high proliferation index (Ki67), high expression of bcl2, bcl-xl, bax and p53, low expression of Rb and caspase 3 and high apoptotic index (Montalban et al, 2004;Rassidakis et al, 2002a;Rassidakis et al, 2002b;Sup et al, 2005;Abele et al, 1997;Brink et al, 1998;Garcia et al, 2003;Montalban et al, 2004;Morente et al, 1997;Smolewski et al, 2000). Evidence has accumulated that the constitutive activation of the NF-B pathway in H/RS cells is of particular importance for explaining the apoptosis deregulation in cHL by up-regulating an anti-apoptotic gene expression program (Bai et al, 2005;Hinz et al, 2002;Hinz et al, 2001;Mathas et al, 2002).…”
Section: Apoptotic and Cell Cycle Pathways In Hlmentioning
confidence: 99%